Fabrication of Plane Transient Diode - An Yu; Zhang Yu Ding; Fu Xing Hua (Institute of Advanced Engineering and Science, 2013)
The fabrication of horizontal structure and vertical structure is proposed based on the parameters of the transient diode, theory is combined with practice in the progress of design, the picture of structural parameters is charted in this paper, establishes the foundation for mading the transient diode with reliability. Transient diode horizontal structure design [is an important element in the design.The mission is based on the request of parameters, selecting the planar geometry of the die and its dimensions. For planar diode, the geometry of die plane is determined by lithography. The design of the transverse structure is the design of the lithographic version of the graphical structure. The area of the base region of the buried layer is known based on the design rules .Buried layer area can roughly calculated, it should be greater than the area of the diffusion of base region andless than the area of the chip. Its widthisto cross above the width of the base region and the opening of the lead hole, i.e. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2389